BLOCKCHAIN AND BLACK ECONOMY: CRYPTOCURRENCY-RELATED CRIMES AND COUNTERMEASURES - Leo S.F. Lin, (Journal of Islamic, Social, Economics and Development, 2024)
This paper proposes an analytical framework based on rational choice theory to examine the opportunities and threats presented by cryptocurrencies and use illicit activities in Taiwan as an example. It discusses the shift from centralized to decentralized financial technology and the utilization of blockchain in various criminal activities such as fraud, exit scams, Ponzi schemes through Initial Coin Offerings (ICOs), and money laundering. The development of virtual currency platforms and exchange companies is explored, with prevalent crime types being organized crime, drug trafficking, fraud, and ransomware. The paper provides case examples of money laundering relating to cryptocurrencies, including online gambling, investment scams, the nexus between cryptocurrency crime and ransomware, and Bitcoin ATMs. Investigative challenges include difficulties in investigating personal off-exchange transactions and enhancing Know Your Customer (KYC) and the Travel Rule in crypto transactions through Financial Institutions (FIs) and Virtual Asset Service Providers (VASPs). Several countermeasures are suggested, such as strategies to increase crime difficulty and cost, enhance regulatory measures for crypto exchange platforms, and promote investigation training and international cooperation. Additionally, the paper underscores the importance of integrating Environmental, Social, and Corporate Governance (ESG) considerations into these countermeasures to address the broader societal and environmental impacts of cryptocurrency-related crimes. This paper contributes to understanding the relationship between blockchain technology, the black economy, and cryptocurrency-related crimes in Taiwan, offering practical countermeasures to combat such illicit activities.